KESEPAKATAN TERHADAP BRAND WONDERFUL INDONESIA: KAJIAN TERHADAP PELANCONG DAN PEGAWAI PEMERINTAH - diah febrina (Jurnal Ranah Komunikasi, 2018)
This study aims to review the agreement in the Visit Indonesia Year tourism marketing strategy through the Wonderful Indonesia brand. This study uses the theory of co-orientation as a theoretical framework. A total of 204 respondents consisting of 110 travelers and 94 government employees in the Ministry of Tourism and Creative Economy of the Republic of Indonesia were interviewed using a set of questionnaires. Based on the results of this study it was found that travelers and government employees did not have an agreement in perceiving Indonesia through the Wonderful Indonesia brand. However, the difference test results based on five elements in the Wonderful Indonesia branding show that travelers and government employees agree that the Indonesian people are friendly people.